Impact of Lockdown on Autopsy Cases in a Tertiary Medical Centre in Northern India: A Retrospective Analysis - Rathore, S; Yadav, A; Kumari , S; Sharma, V; Verma, A K (Journal of Indian Academy of Forensic Medicine, 2022)
2020 will be remembered not only for the COVID-19 pandemic but also for introducing some entirely new concepts like “lockdown” and  “social distancing” which brought the entire world to a standstill. Lockdown approach can have a wide range of implications not just on the  economy but also on the physical, mental and social well-being of the people. We investigated the impact of 78 days nationwide lockdown  in 2020 on profile of the post-mortem cases being brought for autopsy to the mortuary of King George's Medical University, Lucknow,  India. Further 78 days of post lockdown period in 2020 were also included in the study and compared with the corresponding time periods  in 2019. Atotal of 3657 cases were included in the study, 2042 in 2019 and 1615 in 2020. Adjusted odds ratios (aOR) with 95% confidence  intervals (CI) from logistic regression modeling were used to compare the mortality due to different causes across the four study time periods.  Deaths due to RTAs were significantly lower in the lockdown period (aOR = 0.59, CI 0.48, 0.73, p
Keywords: COVID-19; SARS-CoV-2; Autopsy; Lockdown; Mortality